Sala de aula quilombola e o caixote histórico: experiências de um aprendizado significante - SILVA, Maria Cristina da Cruz (2018)
This work aims to show the importance of working with didactic supports to dynamize the Teaching of History in the classroom of Basic Education, due to the need to propose new approaches that allow the expansion of knowledge in the quilombola school environment. The methodology adopted was the bibliographical research that is characterized as an important means of study to elaborate knowledge related to the topic on screen. In this context the theories of historiography and Pedagogy are highlighted as relevant curricular areas in the expansion of historical knowledge. In this discussion, we focus on dialoguing about the local knowledge aired in the quilombola school and highlight the importance of black culture in the formation of Brazilian society, highlighting the specificities of the school space and perceive how the historical knowledge is perceived in the school context. In this perspective, the Historical Crate, idealized didactic product as a result of the learning of the Specialization Course in History Teaching promoted by the Federal University of Pará / Ananindeua University Campus was valued. As for the results we can verify by means of activities with the aforementioned product that it is possible to break traditional practices, developing methods to make the learning of History significant.